2016
DOI: 10.1371/journal.pone.0144274
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Association between Heavy Postpartum Haemorrhage and Postpartum Depression

Abstract: ObjectivesTo explore the association between postpartum haemorrhage (PPH) and postpartum depression (PPD), taking into account the role of postpartum anaemia, delivery experience and psychiatric history.MethodsA nested cohort study (n = 446), based on two population-based cohorts in Uppsala, Sweden. Exposed individuals were defined as having a bleeding of ≥1000ml (n = 196) at delivery, and non-exposed individuals as having bleeding of <650ml (n = 250). Logistic regression models with PPD symptoms (Edinburgh Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 54 publications
2
65
1
Order By: Relevance
“…PPH is the primary cause of postpartum anemia among women without anemia during pregnancy and may increase the risk of PPD by causing postpartum distress and turning delivery into a negative experience . However, PPH has not yet been proven to be a direct risk factor of PPD; a previous cohort study showed a non‐significant association between PPH and symptoms of PPD even while observing a significant association between postpartum anemia . As we were unable to explain the extent to which the observed association between postpartum anemia and PPD may be mediated by PPH in the present study, further studies are warranted to determine if there is a relationship.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…PPH is the primary cause of postpartum anemia among women without anemia during pregnancy and may increase the risk of PPD by causing postpartum distress and turning delivery into a negative experience . However, PPH has not yet been proven to be a direct risk factor of PPD; a previous cohort study showed a non‐significant association between PPH and symptoms of PPD even while observing a significant association between postpartum anemia . As we were unable to explain the extent to which the observed association between postpartum anemia and PPD may be mediated by PPH in the present study, further studies are warranted to determine if there is a relationship.…”
Section: Discussionmentioning
confidence: 55%
“…5 However, PPH has not yet been proven to be a direct risk factor of PPD; a previous cohort study showed a non-significant association between PPH and symptoms of PPD even while observing a significant association between postpartum anemia. 24 As we were unable to explain the extent to which the observed association between postpartum anemia and PPD may be mediated by PPH in Larger, future studies may succeed in detecting the effect of anemia in the second and third trimesters of pregnancy.…”
Section: Discussionmentioning
confidence: 78%
“…In this sample, both EmCS and VE were associated with lower Apgar score and transfer to a neonatal unit, which could initiate existential worries. All those parameters generate a negative delivery experience that could trigger depressive symptomatology .…”
Section: Discussionmentioning
confidence: 99%
“…However, on postpartum day 3, the authors noted that women in the no intervention group only had a 0.78 higher mean physical fatigue score compared with those receiving RBC (physical fatigue scores range from 4 to 20; higher scores indicating more fatigue). These data should not discount the need to consider treatment for postpartum anemia, especially as important maternal morbidities are associated with this condition, including depression, 7274 fatigue, 75 and impaired cognition. 76 These morbidities can negatively impact maternal-child bonding and the mother's ability to provide newborn care.…”
Section: Discussionmentioning
confidence: 99%